Positron emission tomography with computed tomography imaging (PET/CT) for the radiotherapy planning definition of the biological target volume: PART 1. (August 2019) - Alongi, Pierpaolo; Laudicella, Riccardo; Desideri, Isacco; Chiaravalloti, Agostino; Borghetti, Paolo; Quartuccio, Natale; Fiore, Michele; Evangelista, Laura; Marino, Lorenza; Caobelli, Federico; Tuscano, Carmelo; Mapelli, Paola; et al.
Abstract: Aim: Functional and molecular imaging, including positron emission tomography with computed tomography imaging (PET/CT) is increasing for radiotherapy (RT) definition of the target volume. This expert review summarizes existing data of functional imaging modalities and RT management, in terms of target volume delineation, for the following anatomical districts: brain (for primary and secondary tumors), head/neck and lung. Materials and methods: A collection of available published data was made, by PubMed a search. Only original articles were carefully and critically revised. Results: For primary and secondary brain tumors, amino acid PET radiotracers could be useful to identify microscopic residual areas and to differ between recurrence and treatment-related alterations in case of re-irradiation. As for head and neck neoplasms may benefit from precise PET/CT-based target delineation, due to the major capability to identify high-risk RT areas. In primary and secondary lung cancer, PET/CT could be useful both to delimit a tumor and collapsed lungs and as a predictive parameter of treatment response. Conclusion: Taken together, molecular and functional imaging approaches offer a major step to individualize radiotherapeutic care going forward. Nevertheless, several uncertainties remain on the standard method to properly assess the target volume definition including PET information for primary and secondary brain tumors.